2003
DOI: 10.1590/s1415-47572003000300016
|View full text |Cite
|
Sign up to set email alerts
|

Clonal stability of latex yield in eleven clones of Hevea brasiliensis Muell. Arg.

Abstract: Eleven Hevea brasiliensis clones were evaluated for clonal stability of latex yield. A randomized complete block design was used with four replicates, two locations, seven years and three periods per year. Stability analysis was based on clone x year and clone x year x location interactions. Five stability parameters viz environmental variance, shukla's stability variance, regression of clonal latex yield on environmental index, variance due to regression and variance due to deviation from regression were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A crude latex extract from a clone of Malaysian rubber tree Hevea brasiliensis , clone RRIM 600 has been made available for evaluation and was proposed as a candidate allergen for skin test and in in vitro specific serum IgE assays [6,8]. This extract has been widely tested as a skin-testing reagent and has been evaluated by the multi-center latex skin testing study task force with success, although the clone is classified as an unstable phenotype with variability in the latex composition [9]. Crude extracts are not appropriate candidates as standardized antigens due to their variability, lack of dependability, irrelevant cross reactivity, and questionable safety in in vivo use such as skin testing.…”
Section: Introductionmentioning
confidence: 99%
“…A crude latex extract from a clone of Malaysian rubber tree Hevea brasiliensis , clone RRIM 600 has been made available for evaluation and was proposed as a candidate allergen for skin test and in in vitro specific serum IgE assays [6,8]. This extract has been widely tested as a skin-testing reagent and has been evaluated by the multi-center latex skin testing study task force with success, although the clone is classified as an unstable phenotype with variability in the latex composition [9]. Crude extracts are not appropriate candidates as standardized antigens due to their variability, lack of dependability, irrelevant cross reactivity, and questionable safety in in vivo use such as skin testing.…”
Section: Introductionmentioning
confidence: 99%
“…On rubber tree, a large number of studies on genotypeenvironment interactions were conducted in Sri Lanka (Jayasekera 1983; Jayasekera et al 1994;Withanage et al 2005), Indonesia (Daslin et al 1986), Nigeria (Onokpise et al 1986;Omokhafe & Alika 2003;Omokhafe et al 2004a, b), Malaysia (Tan 1995), India (Menattoor et al 1991) and Brazil (Gonçalves et al 1992(Gonçalves et al , 1998(Gonçalves et al , 1999(Gonçalves et al , 2003(Gonçalves et al , 2008(Gonçalves et al , 2009Costa et al 2000;Gouvêa et al 2012;Silva et al 2013Silva et al , 2014. Several of these studies used the method developed by Eberhart and Russell (1966) to determine the genotype × environment interaction on growth and/or latex yield of Hevea clones (Gonçalves et al 1992(Gonçalves et al , 2003(Gonçalves et al , 2008(Gonçalves et al , 2009Omokhafe & Alika 2003;Omokhafe et al 2004a, b;Gouvêa et al 2012;Silva et al 2013Silva et al , 2014. It was reported that adaptability and stability analyses involving statistical procedures allow the identification of Hevea clones of which the performance is more stable and responses to the environmental variations are predictable (Silva et al 2014).…”
Section: Introductionmentioning
confidence: 99%